Energy performance of an evacuated tube solar collector using single walled carbon nanotubes nanofluids. (15th November 2015) - Sabiha, M.A.; Saidur, R.; Hassani, S.; Said, Z.; Mekhilef, Saad
Highlights: Collector efficiency is found to be 71.84% higher with SWCNT nanofluid than water. Thermal performance of an ETSC is studied with varying mass flow rates. Collector efficiency is investigated with 3 vol.% of SWCNT nanofluids. Maximum collector efficiency is found 93.43% with SWCNT (0.2 vol.%) nanofluid. An empirical correlation of thermal efficiency is developed. Abstract: An experimental study was performed to determine the thermal efficiency of an Evacuated Tube Solar Collector (ETSC) using water based Single Walled Carbon Nanotubes (SWCNTs) nanofluids. Experiments were carried out using SWCNTs nanofluids having volume concentrations of 0.05, 0.1, and 0.2 vol.%. The performance of the collector was compared with SWCNTs nanofluid and water using the flow rates of 0.008, 0.017, and 0.025 kg/s. The experiments were undertaken according to ASHRAE standard 93-2003. The results show that, the collector efficiency improved with SWCNTs nanofluids compared to water as a working fluid. The maximum efficiency found to be 93.43% for 0.2 vol.% SWCNTs nanofluids at a mass flow rate of 0.025 kg/s. The collector efficiency shows greater enhancement with the increasing volume fractions of SWCNT nanoparticles and flow rate. In conclusions, results suggest that SWCNTs nanofluids can be used as the working fluids in an ETSC to absorb heat from solar radiation and to convert solar energy into thermal energy efficiently.